Consumers' experience with hospitality and tourism technologies: Measurement development and validation. (September 2022) - Shin, Hyejo Hailey; Jeong, Miyoung; So, Kevin Kam Fung; DiPietro, Robin
Abstract: As new and emerging technologies continue to transform hospitality and tourism operations and consumer environments, understanding consumers' experience with hospitality and tourism technologies has become an urgent issue. This study aimed to develop a theoretically sound conceptualization of consumers' experience with hospitality and tourism technologies. Employing a sequential exploratory approach and scale development procedures, this study theoretically defined and conceptualized consumers' technology experience as a second-order formative construct consisting of nine dimensions (sensorial, cognitive, pragmatic, emotional, relational, unique, familiar, controllable, and economical experiences). This study also developed a set of scales to measure consumers' experience with hospitality and tourism technologies, and empirically assessed and validated the developed scale. The results demonstrated that the developed scale exhibited robust psychometric properties. The developed scale is applicable to most hospitality and tourism technologies and various sectors of the hospitality and tourism industry. Highlights: Conceptualized consumers' experience with hospitality and tourism technologies. Identified the nine dimensions of consumers' technology experience. Developed a set scale to measure the second-order construct of technology experience. Validated the developed scale for consumers' technology experience. Empirically investigated the consequences of technology experience.